Reception aesthetics in techniques Theatrical show (Journal of the College of Basic Education, 2023)
At the beginning of the twentieth century and the decades that followed, the feeling towards art changed, and the artistic taste changed, as a result of new ideological conflicts and as a result of cultural change, which caused a beautiful change in the mentality of the recipient, and included the subject of artwork in general and theater in particular.The effect of this aesthetic change on the art form, which is compatible with the concept of material involved under a certain philosophy, and since the theater depicts reality, and this portrayal does not become possible without knowledge of dialectics.Accordingly, the visual image has become a direct relationship with the actual reality, and demolition and construction has become a method of arbitration in the image.From these trends emerged the modern philosophical aesthetic thought, which included Hegel, Marx, Heidegger, Sartre, and Al-Birkamo. This thought explores the issues of society, represented by freedom and social conflict, which later became a material for theatrical presentation, as we find the organic connection between the theater and the cultural change of society at the level of aesthetics and at the level of reception, which reached in its clarity to the point that made a number of intellectuals and theater workers express the importance of this influence In this sense, we find that Abia and Craig have dealt with the aesthetic intellectual premises of their reality and their employment in the theatrical performance to stimulate awareness and aesthetic perception of the recipient. By changing the codes of the dramatic elements and means at the level of the presentation mechanism and the mechanism of the aesthetically pleasing image, represented by decoration, lighting, costumes, make-up, and the actor, and through the components of the structural structures of these elements and their impact on the recipient.